Supplemental Material: Neogene sedimentary record of the evolution of a translated strike-slip basin along the Denali fault system: Implications for timing of displacement, composite basin development, and regional tectonics of southern Alaska - Wai K. Allen (11615125) (2021)
Ar/Ar geochronologic and U-Pb detrital zircon geochronologic ages.